Pengaruh Suku Bunga Pinjaman dan Promosi Terhadap Keputusan Kredit Pensiun di Bank Mandiri Taspen KCP Leuwiliang - Agus Resmanto; Vivi Ristanti; Lily Zulaeha (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2026)
The increasingly competitive banking industry encourages banks to optimize credit distribution, including in the pension segment, which has stable income and relatively low risk. This segment is considered potential due to its income stability, which can reduce the risk of non-performing loans. However, in practice, credit decisions are not only influenced by economic factors such as interest rates, but also by marketing strategies such as promotion implemented by banks. This study aims to analyze the effect of loan interest rates and promotion on pension credit decisions at Bank Mandiri Taspen Sub-Branch Leuwiliang. This research uses a quantitative approach with a causal associative design. The population consists of 1,032 customers, with a sample of 100 respondents determined using the slovin formula and accidental sampling technique. Data were collected through Likert-scale questionnaires and analyzed using multiple linear regression. The results show that partially, loan interest rates have no significant effect on credit decisions, while promotion has a positive and significant effect. Simultaneously, both variables have a significant effect, with a coefficient of determination of 0.244. These findings differ from some previous studies that found a significant effect of interest rates, but are consistent with studies emphasizing the. The implications of the research show that promotion is a dominant factor in driving credit decisions, so banks need to optimize promotional strategies that are effective, targeted, and based on the needs of retired customers.